Preservation treatments of Bambusa vulgaris vittata against the attack of Dinoderus minutus - Cortez-Barbosa, Juliana; Martines Morales, Elen Aparecida; Higuti, Karina Arakaki; Alves, Ana Clara Lancarovici; De Araujo, Victor Almeida; Gava, Maristela; Garcia, José Nivaldo (Instituto de Ecología, A.C., 2019)
Bamboo canes are a unique construction raw material for several types of structures, and there is a growing acceptance of bamboos for structural uses. However, they have as a disadvantage their propensity to attack by insects. In this work, a study of the effectiveness of three different types of preservatives was made with: 1) traditional chemicals, 2) natural substances with low risk to humans and 3) thermal at different temperatures to prevent the Dinoderus minutus beetle attack to Bambusa vulgaris vittata bamboo species. The first two treatments were performed by immersion, and thermal type was made by a drying process. Every two weeks, the attack on three specimens of each treatment was evaluated, including those corresponding to a control specimen without any preservation element. The results showed that most of the treatments by immersion were effective, reducing considerably the attack of the insects in comparison with the control. As for the heat treatment, temperatures less than or equal to 130 °C did not prove to be effective; temperatures of 190 °C and 210 °C revealed acceptable efficiencies.